Studies in law, politics, and society. Vol. 39 - Sarat, Austin (Amsterdam ; Oxford : Elsevier JAI, 2006)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work covers political science, policy studies, and law. Some of the articles published in this issue focus on the sources of conflict and violence as well as law's response to both. Here, research illustrates the complex ways law can be said to be both opposed to violence and yet be violent itself. Other articles focus on the way judges and other legal actors use law as they interpret it. Taken together they exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship. An interdisciplinary volume that discusses political science, policy science and law, this book is divided into two parts: conflict, violence, and legal processes; and deciding cases, charting progress. It uses case law examples to examine issues.
Description based on print version record.
Keywords: Sociological jurisprudence; Political sociology; Anthropology; Political Science -- General; Social Science -- Criminology